2020
DOI: 10.3390/vaccines8040609
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome In-Silico Analysis of South African G1P[8] Rotavirus Strains before and after Vaccine Introduction over a Period of 14 Years

Abstract: Rotavirus G1P[8] strains account for more than half of the group A rotavirus (RVA) infections in children under five years of age, globally. A total of 103 stool samples previously characterized as G1P[8] and collected seven years before and seven years after introducing the Rotarix® vaccine in South Africa were processed for whole-genome sequencing. All the strains analyzed had a Wa-like constellation (G1-P[8]-I1-R1-C1-M1-A1-N1-T1-E1-H1). South African pre- and post-vaccine G1 strains were clustered in G1 lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Previous studies have shown that the VP5* and VP8* outer capsid proteins play a significant role in inducing neutralising antibodies against rotaviruses (Ludert et al 2002;Park et al 2021;Ruggeri and Greenberg 1991;Zhao et al 2015). The VP5* protein of the Malawian G3P[8] strains were 100% conserved when compared to that of Rotarix vaccine, consistent with previous studies that have reported that the VP5* is a highly conserved protein (Rasebotsa et al 2020;Mwangi et al 2020). However, we identified E150D nonsynonymous substitutions within the VP8*-1 antigenic region and S125N, S131R and N135D substitutions within VP8*-3 antigenic region when we compared the VP4 (VP8*sub-unit) segments of our G3P [8] strains to that of the strain used in the Rotarix rotavirus vaccine.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Previous studies have shown that the VP5* and VP8* outer capsid proteins play a significant role in inducing neutralising antibodies against rotaviruses (Ludert et al 2002;Park et al 2021;Ruggeri and Greenberg 1991;Zhao et al 2015). The VP5* protein of the Malawian G3P[8] strains were 100% conserved when compared to that of Rotarix vaccine, consistent with previous studies that have reported that the VP5* is a highly conserved protein (Rasebotsa et al 2020;Mwangi et al 2020). However, we identified E150D nonsynonymous substitutions within the VP8*-1 antigenic region and S125N, S131R and N135D substitutions within VP8*-3 antigenic region when we compared the VP4 (VP8*sub-unit) segments of our G3P [8] strains to that of the strain used in the Rotarix rotavirus vaccine.…”
Section: Discussionsupporting
confidence: 87%
“…However, we identified E150D nonsynonymous substitutions within the VP8*-1 antigenic region and S125N, S131R and N135D substitutions within VP8*-3 antigenic region when we compared the VP4 (VP8*sub-unit) segments of our G3P[8] strains to that of the strain used in the Rotarix rotavirus vaccine. These substitutions have been associated with lineage III strains that are currently predominant in eastern and southern African countries where the Rotarix vaccine is used (Rasebotsa et al 2020; Mwangi et al 2020; Maringa et al 2021). We speculate that the structural changes we observed in the VP8*-1 and VP8*-3 antigenic regions could reduce the binding of the vaccine-induced antibodies thereby reducing the vaccine effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extracted viral dsRNA was subjected to cDNA synthesis using the Maxima H Minus Double Stranded Synthesis Kit (Thermo Fisher Scientific, Waltham, MA, USA), as described previously [ 41 ]. The DNA libraries were prepared utilizing the NexteraXT DNA Library Preparation Kit (Illumina, San Diego, CA, USA) as per the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%